Fracture union and complication following internal fixation of clavicle by plate and screw - Patro, Bishnu Prasad; Patra, Saroj Kumar; Mohapatra, Subrat (International Journal of Research in Medical Sciences, 2016)
Background: Among all long bones clavicle is the only bone placed horizontally and has membranous ossification. Clavicle fractures accounting for about 2.6% of total body fractures and 34% to 45% of total shoulder girdle injuries in adults. Most fractures occur in middle third of clavicle and common in young male patients. It has wide range of management from conservative to variant internal fixation. Each procedure has its own outcome and complications. We tried to find out the outcome and complications following internal fixation of clavicle with plate and screws. Methods: In a prospective study 50 patients of fracture mid shaft clavicle who were treated with plate and screw were followed for a period of two years. Only adults more than 18 years were included in the study. All patients were followed at 2nd post-operative day 5th post-operative day 14th post-operative day and at 1, 2, 6, 12 and 24 months. Only two parameters were observed i.e. union of fracture and post-operative complications. Results: Of all patients operated with plate and screw 48 patients had good radiological union by six months. Only two patients had non-union and one with implant failure at 12 months. Of complications one had stitch abscess and seven had hardware discomfort. Conclusions: Clavicle fracture in adults has multimodal treatment option. Though conservative management has good results it has high chance of mal-union and non-union. Operative fixation should be opted for adult individuals where chance of non-union is high. Plate and screw fixation has good results in terms of union with least complication.